Study on the microstructure and properties of laser-cladded AlCoCrFeNiCu0.5-xNbₓ high-entropy alloy coatings - Mingsai Zhang; Shufeng Sun; Jin Wang; Fengyun Zhang; Yadi Wang (PLoS ONE, 2026)
In this study, the high-entropy alloy AlCoCrFeNiCu0.5 − xNbx (x = 0, 0.1, 0.2, 0.3, 0.4, 0.5) is selected as the research subject. Coatings with varying Cu/Nb ratios are fabricated by laser cladding. The phase composition, microstructure, microhardness, tribological behavior, and corrosion resistance are systematically investigated. The results reveal that when x = 0.2, the coating exhibits a dual-phase structure consisting of FCC and Laves phases. A large cellular structure forms and maintains good microstructural continuity. The coating shows a low friction coefficient of 0.327, and no significant spalling is observed on the worn surface. In both 3.5% NaCl and 0.5 M H₂SO₄ solutions, the coating exhibits the most positive corrosion potential, the lowest corrosion current density, and the highest polarization resistance, indicating excellent electrochemical stability.